Seorang Laki-Laki dengan Tumor Mediastinum Posterior (Malignant Peripheral Nerve Sheath Tumor): [Malignant Peripheral Nerve Sheath Tumor in a Man: A Case Report] - Daniel Maranatha; Shinta Karina Yuniati (Jurnal Respirasi, 2016)
Background: Malignant tumors arising from peripheral nerves or displaying differentiation along the lines of the various elements of the nerve sheath are referred to Malignant peripheral nerve sheath tumors (MPNST) and also called malignant schwannomas or neurofibrosarcomas. The common sites of involvement are head, neck, extremities and thorax. This case was discussed due to its rare incidence, namely less than 5% of soft tissue malignant tumor. The overall five year survival rate is approximately 50% in patients with resectable tumor. Case: We report a case of MPNST arising from mediastinum, the patient was a male, 41-years-old, with chief complaint are chest pain and mass in the back. Contrast enhanced chest CT Scan showed a solid mass (10.02 × 6.97 × 10.53 cm) in the right side of the posterior mediastinum. On microscopic examination with hematoxylin eosin imunostaining, of the mass on mediastinum showed typical features of MPNST, which were positive for S-100 imunostaining. Based on convensional histopathologic and imunostaining, this case was concluded as Malignant peripheral nerve sheath tumors (MPNST). Conclusion: The treatment of chest wall MPNSTs is multimodality, including wide local excision, adjuvant radiotherapy, and chemotherapy. In our case, we performed direct excision due to the infiltrating mass to the surrounding tissue, so the prognosis for this case was good. This case indicates the role of chemotherapy in treatment of advanced MPNST. Studies shows the superiority of the doxorubicin–ifosfamide regimen. As in this case the patient showed complete respons after surgery and adjuvant chemotherapy.